Purely cutaneous rosai-dorfman disease with immunohistochemistry - Uzma Farooq; Anna H Chacon; Vladimir Vincek; George W Elgart (Wolters Kluwer Medknow Publications, 2013)
Background: The cutaneous form of Rosai-Dorfman disease (RDD) is a rare entity that manifests solely with skin papules or nodules and does not present with the usual myriad of symptoms of classical RDD. Aims: To analyze the most recent publications regarding cutaneous RDD to point out updated, relevant aspects regarding future directions for clinical recognition and management. To identify histopathologic and immunohistochemical findings in skin lesions that permit diagnosis. Materials and Methods: We present a case of a gentleman with a history of multiple lipomas with a new solitary nodule on physical exam; microscopic examination shows the typical findings of RDD with the associated diagnostic immunohistochemical profile, as well as the expected finding of histiocytes engulfing other intact inflammatory cells. Results: Our patient was managed with surgical excision of the entire lesion, one of the several available treatment options. Long-term follow-up 2 years later did not reveal any complications, recurrences, or new lesions. Conclusion: The diagnosis of cutaneous RDD is differentiated from other histiocytic conditions by the combination of clinical findings accompanied by histopathologic and immunohistochemical confirmation.